Metabolic rewiring controlled by HIF-1α tunes IgA-producing B-cell differentiation and intestinal inflammation - Meng, Xianyi; Asadi Asadabad, Sahar; Cao, Shan; Song, Rui; Lin, Zhen; Safhi, Mohammed; Qin, Yi; Tcheumi Tactoum, Estelle Manuella; Taudte, Verena; Ekici, Arif Bülent; Mielenz, Dirk; Wirtz, Stefan; et al. (Cellular & Molecular Immunology, 2024)
Germinal centers where B cells undergo clonal expansion and antibody affinity maturation are hypoxic microenvironments. However, the function of hypoxia-inducible factor (HIF)-1α in immunoglobulin production remains incompletely characterized. Here, we demonstrated that B cells lacking HIF-1α exhibited significantly lower glycolytic metabolism and impaired IgA production. Loss of HIF-1α in B cells affects IgA-producing B-cell differentiation and exacerbates dextran sodium sulfate (DSS)-induced colitis. Conversely, promoting HIF-1α stabilization via a PHD inhibitor roxadustat enhances IgA class switching and alleviates intestinal inflammation. Mechanistically, HIF-1α facilitates IgA class switching through acetyl-coenzyme A (acetyl-CoA) accumulation, which is essential for histone H3K27 acetylation at the Sα region. Consequently, supplementation with acetyl-CoA improved defective IgA production in Hif1a-deficient B cells and limited experimental colitis. Collectively, these findings highlight the critical importance of HIF-1α in IgA class switching and the potential for targeting the HIF-1α-dependent metabolic‒epigenetic axis to treat inflammatory bowel diseases and other inflammatory disorders.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B cells; HIF-1α; Hypoxia; IgA; Intestinal inflammation